Explicating the Strategic Options of Fiskars’ English & Crystal Living Business in the Future of Ethical Luxury - Nwoko, Ogadinma (My University, 2022)
The English & Crystal Living Business unit of Fiskars (hereinafter E&CL) emphatically sees its strategic futures within a business context defined by ethical luxury. Accordingly, E&CL seeks to apply a Futures perspective towards defining ethical luxury. For E&CL, the overarching idea is that by applying a Futures perspective towards the definition of ethical luxury it would be better suited to elevate its value offerings to the level of ethical luxuries already in nearer future, well into the farther future. This dissertation has been sponsored by Fiskars and is aimed at conceptualizing what ethical luxury could mean for the company, from a Futures perspective. Accordingly, this dissertation has been guided by the following research questions. Firstly, if one deconstructs the term ethical luxury into its constituent elements – ethics and luxury, with the emphatic goal of understanding how said elements could be understood in the future, how does one reconstruct a Futures-oriented definition of ethical luxury? Precisely, which factors underlie said Futures-oriented definition? Secondly, based on the Futures principle of alternative realities, can we envisage the possibility of alternative factors underlying said Futures-oriented definition of ethical luxury? Should distinct factors be discerned, could one envisage alternative modes of understanding said discerned factors? Last but not least, on the basis of the pinpointed factors underlying said possible Futures-oriented definition of ethical luxury how can Fiskars E&CL elevate its wares and value offerings to the level of ethical luxuries? This dissertation identified sustainability and authenticity as ethical factors that underlie a possible Futures-oriented conceptualization of the term ethical luxury. Accordingly, by minimizing aspects of operations that result in negative socioeconomic and environmental consequences (for instance through adopting circular economy business models), and by implementing policies that result in positive socioeconomic and environmental outcomes (for instance through CSR and philanthropy), organisations adhere to the principles of sustainability. In a similar way, organisations display authenticity to the extent that they subscribe to such authenticity drivers as originality, variability in craftsmanship, and respect for local/traditional knowledge. Meanwhile, in line with the futures principle of ‘alternative renderings of reality’, based on the interviews and on the conduction of Causal Layered Analysis on the findings from said interviews, this dissertation discerned alternative modes of understanding sustainability and authenticity. Accordingly, sustainability further entails removing inefficiencies and waste across luxury value chains, as well as entails a recourse back to localized economies. Both narratives, in a nutshell, posit a need to limit an organization’s aggregate ecological footprint, hence that of the consumers of its products as well. Authenticity, for luxury producers further entails positioning themselves as authentic to the extent that they support characteristics that are deemed authentic – for instance human/local knowledge. Meanwhile, this dissertation posits that all modes of understanding sustainability and authenticity ought to ultimately be embedded into a conceptualization of luxury, whose future not only involves the consumption of tangible forms of it, but also involves the consumption of experiential/intangible forms of it. On the basis of the mentioned modes of understanding sustainability and authenticity, as factors underlying a Futures oriented conceptualization of ethical luxury, an ideation workshop was held involving key decision makers of E&CL. The goal of the workshop was to ideate how E&CL’s value offerings could be elevated to the level of ethical luxuries. An example of an idea generated from the workshop includes the following. An ethical dimension could be added to a product already deemed luxurious by ensuring that said product has been made by local underprivileged youths, who E&CL have themselves enabled to develop a skill in handmade artistry.
Keywords: Ethical luxury, sustainability, authenticity, Futures oriented, alternative modes of understanding